KOMUNIKASI ORANG TUA – REMAJA DENGAN SIKAP REMAJA MELAKUKAN HUBUNGAN SEKSUAL PRANIKAH - Budi Punjastuti; Laly Mualifah (Jurnal Keperawatan Notokusumo, 2017)
Background : The negative impact of premarital sexual intercourse due to the low knowledge of adolescents on reproductive health and rights, including, positioning adolescents in at-risk groups. Effective communication of parents - adolescents has been identified as a major strategy in promoting responsible sexual behavior and minimal sexual experience on. Methods : This study is an analytic study and observational study with cross sectional study design. Research location in Badran Yogyakarta. Sampling is done by cluster random sampling. Result : Based on the result of statistical test by using t test, there is a significant correlation between respondent's characteristic and parent's characteristic toward respondent attitude, with p value = 0,00 (p <0,05). Based on the result of bivariable statistic test, obtained p value = 0,00 (p<0,05) which have meaning there is correlation between parent- teen communication with adolescent attitude of premarital sexual intercourse. Conclusions : The average score of adolescent attitudes toward premarital sexual intercourse on poor parents communication is higher than that of good parent communication. Parental education and employment are characteristic factors of parents associated with adolescent attitudes toward premarital sexual intercourse.